SUB-CHRONIC ORAL TOXICITY ASSESSMENTS OF BANIKHA HARD CAPSULE IN WISTAR RATS - Dang, Thi Thu Hien (Tạp chí Sinh lý học Việt Nam, 2024)
Banikha is a formula originating from herbal medicines used to improve and treat some diseases such as immunostimulatory activity and improve physical strength; however, to our knowledge, no systematic study concerning its toxicity profile has been reported. Therefore, this study aimed to evaluate the potential sub-chronic toxicity of Banikha hard capsules in experimental animal. The sub-chronic toxicity study was carried out in Wistar rats for 12 consecutive weeks by oral administration at doses of 0.385 and 1.155 g/kg/day (n = 10/group). The general behavior and body weight of the rats was observed daily. Biochemical, hematological, macroscopically, and histopathological examinations of several organs were conducted at the end of the treatment period. After treatment, Banikha induced no mortality or treatment-related adverse effects with regard to body weight, general behavior, or hematological, and biochemical parameters. Histopathology assessment did not show any significant variation between control and treatment groups during the study period. In conclusion, the present study revealed that oral administration of Banikha hard capsule for 12 weeks, at dosages did not induce toxicological damage in rats.